FOUR STOCK SPLIT THEORIES: A STUDY ON INDONESIAN CAPITAL MARKET YEAR 2003-2007 - FATHIA MAISA SYAFURAH, SITI
In our country, capital market is growing rapidly, especially since 2003. The Indonesian capital market is being chosen by investors as an attractive investment tool. Many studies have been conducted by academician and researchers about actions regarding capital market, one of those actions are stock splits. Although there have been numerous studies of stock split, there have not been any joint research upon the topic of stock split theory. The need to identify what initially motivates executives to commence stock split comes to the mind of the writer. The purpose is to examine which theory best suits Indonesian stock splits (whether it is trading-range or neglected firms), and to find evidence of increase in frequency (liquidity), and/or in operating income (signaling). There are many theories concerning why managers initiate stock split, what causes it, and what is its effect to the firms. Three of the most known theories are trading-range, liquidity, and signaling theory, while a more infrequent one is the neglected firms’ theory. Trading-range and liquidity has similar notions, while the other two are different. This paper uses multiple logistic regression, which is widely used by educators and researchers, due to the dependent variable being a binary variable. Furthermore, the hypothesis test will use the chi square for assessing its significance. The result indicates that there is significant evidence for a higher price in the share price of stock splitting firms in previous years in comparison to other firms in the same sector (which concludes to the trading-range theory), and there is a higher level of trading frequency after the commencement of stock split, in comparison to the change for trading frequency of the same sector where the firms belong to. Furthermore, it did not find any significant relation to the increase in operating income, nor did it find evidence of smaller firm sixe (visibility) on those who split market worth, thus rejecting to the signaling, and neglected firm’s theory.